The discovery of dabigatran etexilate for the treatment of venous thrombosis - Feuring, Martin; Ryn, Joanne van (Expert opinion on drug discovery, 2016)
Introduction: Venous thromboembolism (VTE) can be life-threatening and requires anticoagulant treatment; for many years, vitamin K antagonists, e.g. warfarin, were the only oral anticoagulants available for long-term treatment. Although highly effective, they have many limitations including a slow onset, a multitude of drug-drug and drug-food interactions, and a narrow therapeutic range. These limitations spurred the search for non-vitamin K antagonist oral anticoagulants (NOACs), such as dabigatran etexilate.Areas covered: The authors illustrate the progression of preclinical and clinical studies leading to the development of dabigatran, the only approved NOAC to act by direct thrombin inhibition. They focus on molecule discovery, animal models of thrombosis, clinical trials and post-launch activities in VTE treatment.Expert opinion: Dabigatran demonstrated comparable efficacy to the highly effective warfarin, and a more favourable safety profile in trials of VTE treatment. A favourable anticoagulant safety profile in addition to efficacy is essential for VTE treatment. Availability of the dabigatran-specific reversal agent, idarucizumab, provides a means of rapidly reversing the anticoagulant effect if required. Future investigations into the optimal duration of VTE treatment and an evaluation of the impact of idarucizumab, in real-world studies, could provide valuable information to help optimise treatment for selected patients.
Gesehen am 17.10.2019